Students’ Perceptions: Utilizing WhatsApp and Google Classroom for Learning English in Covid-19 Pandemic - Arum Sekar Nurhijannah (Institut Agama Islam Negeri (IAIN) Manado, 2022)
Online learning is implemented due to the Coronavirus Disease-19. This implementation is intended to avoid the spread of the virus. This study is qualitative research aimed at students’ perceptions and the effectiveness of using WhatsApp and Google Classroom to learn English throughout the pandemic era. This study consists of 37 students in SMP Negeri 1 Galur. All the participants are seventh-grade students. The participants are required to respond to all the statements written in the form of a questionnaire. The questionnaire is individually administered online using Google Forms. This study reveals that students found it helpful and effective in utilizing both applications even though there are some obstacles while utilizing the application. This study was conducted to find out the benefits and effectiveness of using technology in learning during the COVID-19 pandemic